A simple method for assessing the binding of concanavalin A to mononuclear cell surfaces: no interference of visceral leishmaniasis serum on this binding - Manoel Barral-Netto; A. Barral (Memorias do Instituto Oswaldo Cruz, 1986)
We report a simple method for evaluating the binding of concanavalin A (ConA) to human peripheral blood mononuclear cells (PBMC). The binding is evidenced by an immunoenzymic assay using peroxidase-conjugated immunoglobulins of a rabbit anti-ConA serum. Using the method we show that sera from patients with American leishmaniasis do not interfere with binding of ConA to PBMC.